Kasih yang Sejati Mengasihi Allah dan Sesama Manusia dari Sudut Pandang Bimbingan dan Konseling - Ernawati, Renatha; Nugroho, Andreas Rian; Wigunawati, Eustalia; Gunawan, Ronny (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
University Christian of and SMA PGRI Lubang Buaya collaborated on a Community Service project for Christian students, focusing on the theme "True Love: Loving God and Fellow Humans from a Guidance and Counseling Perspective." The event took place on March 19, 2025, during the month of Ramadan. A total of 16 teenagers aged 16-19 years old participated in the activity. Through a brief worship session, material presentation, discussion, and games, students were given an understanding of the theme. The evaluation results showed a significant increase in students' knowledge and attitudes. After participating in the activity, participants' understanding of True Love: Loving God and Fellow Humans from a Guidance and Counseling Perspective improved. Prior to the activity, most participants did not understand that love from God and fellow humans could help them discover their potential. The successful collaboration with SMA PGRI can serve as a model for similar activities in the future.